Pengaruh Pengungkapan Corporate Social Responsibilty (CSR) terhadap Corporate Value - Yunita Eriyanti Pakpahan; Yanita Manda Sari (J-MAS (Jurnal Manajemen dan Sains), 2022)
The highest scoring instrument in CSR assessment is the Sri Kehati index if compared to LQ45 and IHSG. With the application of CSR in the company will increase the value of the company so that investors can consider in investing their capital..This study aims to analyze the effect of corporate social responsibility on corporate value in companies indexed by Sri Kehati. The study was conducted on companies listed on the Sri Kehati index listed on the Indonesia Stock Exchange for the period 2016 – 2020. The sample size was 10 (ten) companies with secondary data on annual financial reports from the Indonesia Stock Exchange or the company's website. Data analysis was carried out using simple linear regression statistical methods and hypothesis testing with t-test. The results of the study show that the disclosure of CSR values has an effect on firm value.